Receptor identification for alarmins and DAMPs - Oppenheim, Joost J. (Henry Stewart Talks, 2011)
Definition of Alarmins and Damps, History of discovery that antimicrobial peptides such as Beta Defensins recruit and activate immune cells engaged in host defense, Identification of other antimicrobials such as granulysin and nuclear binding factors, e.g. HMGN1, as also acting as alarmins that activate receptors on host cells, Proposal to use some alarmins as vaccine adjuvants